Music & Memory: The Impact of Individualized Music Listening on Depression, Agitation, and Positive Emotions in Persons with Dementia. Issue 1 (2nd January 2021) - Huber, Andreas; Oppikofer, Sandra; Meister, Laura; Langensteiner, Fabian; Meier, Nico; Seifert, Alexander
ABSTRACT: This study aimed to investigate the impact of a music-based intervention on depression, agitation, and positive emotions among 23 persons with dementia, using a crossover design. Along with a caregiver, each participant received a total of 16 sessions of individualized music listening. All sessions were filmed, resulting in 362 videos, and the content was analyzed. Depression scores decreased significantly over time while agitated behavior showed a constant moderate level without any significant decreases. Positive emotions occurred significantly more often than negative emotions during the music listening. Individualized music listening induced positive emotions and reduced depression scores over time.